2019
DOI: 10.1002/14651858.cd004477.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological agents for adults with acute respiratory distress syndrome

Abstract: Background Acute respiratory distress syndrome (ARDS) is a life-threatening condition caused by direct or indirect injury to the lungs. Despite improvements in clinical management (for example, lung protection strategies), mortality in this patient group is at approximately 40%. This is an update of a previous version of this review, last published in 2004. Objectives To evaluate the e ectiveness of pharmacological agents in adults with ARDS on mortality, mechanical ventilation, and fitness to return to work a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
136
0
10

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(154 citation statements)
references
References 140 publications
(9 reference statements)
2
136
0
10
Order By: Relevance
“…Our search for systematic reviews of ARDS identified 836 citations; we ultimately chose a systematic review published in 2019 as the target for updating. 29 Our search for primary studies identified 1 new eligible RCT published in 2020. 30 Including 6 RCTs identified from the previous review, we included 7 RCTs 30-36 with 851 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Our search for systematic reviews of ARDS identified 836 citations; we ultimately chose a systematic review published in 2019 as the target for updating. 29 Our search for primary studies identified 1 new eligible RCT published in 2020. 30 Including 6 RCTs identified from the previous review, we included 7 RCTs 30-36 with 851 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, in reference to ARDS, at the moment there is very low evidence on the positive effect of the treatment in this critical condition [54]. There is not conclusive evidence that supports the use of GCs in the treatment of viral respiratory infection and their use remains controversial in COVID-19 [52].…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…A review of treatments for acute respiratory distress syndrome of any cause, based on six studies with a total of 574 patients, 19 concluded that insufficient evidence exists to recommend corticosteroid treatment. 20 Septic shock has been reported in seven (5%) of 140 patients with 2019-nCoV included in published reports as of Jan 29, 2020. 3,18 Corticosteroids are widely used in septic shock despite uncertainty over their efficacy.…”
mentioning
confidence: 99%